Possibilities of Kipchak Dialects in filling the Lexicon of Uzbek Language - Khasanov Abdumannon Majidovich (International Journal on Integrated Education, 2021)
This article is devoted to filling the lexical gaps in the Uzbek language with of Kipchak dialects. The proverb shows the norms and criteria for enriching lexical lacunae in modern Uzbek with dialektal word. The mechanisms of application of these criteria are explained by examples. These principles are specific to most languages and are formed in a particular language on the basis of the literary norms of that language. In the course of the research, the gaps identified in the process of comparing the lexicon of the Uzbek literary language and folk dialects were analyzed. That is, the lexical lacuna b in literary language represents dead concepts the popularity of dialectics. Dialektal word in Kipchak dialects have been studied to delineate and define the object of study. Becoming a literary unit deemed appropriate for the interpretation of the meaning of the dialectism lenses and related sentences. It is based on the need to introduce into the lexicon of literary language of dialektal word that are actively used in folk dialects. Recommendations were made to continue working in this direction. In summary, the purity of the language blower to ensure the development of the city and its lexical gaps start to fill the need for serious attention